H2. Maternal hemodynamic status in pregnancies complicated by intrauterine growth restriction (IUGR) and post-partum follow up. (12th August 2016) - Di Martino, D.; Zullino, S.; Casati, D.; Grimaldi, A. S.; Sterpi, V.; Principato, G.; Garbin, M.; Ferrazzi, E.
Abstract: Aims : To investigate maternal hemodynamic status in pregnancies complicated by IUGR and in the post-partum. Methods : In this prospective study, we enrolled pregnant women between 24 and 38 weeks divided in severe and mild IUGR and a group of controls matched for gestational age. Severe IUGR was defined as abdominal circumference <5th centile and a Doppler velocimetry in umbilical artery42SD. Mild IUGR was defined as an abdominal circumference <10th centile and a Doppler velocimetry in umbilical artery <2SD. A cardiologist performed maternal echocardiographies at diagnosis and 6–12 weeks post-partum, to calculate cardiac output (CO), total vascular resistance (TVR) and indexes of diastolic dysfunction evaluated with tissue Doppler (E0/A0). Results : We recruited 14 severe IUGR, 43 mild IUGR and 19 controls. CO was significantly decreased and TVR significantly increased in IUGR compared to controls. The group of severe IUGR showed the highest values. Only severe IUGR showed a decrease of the heart rate during pregnancy and maintains a low CO in the post-partum. Discussion : The hemodynamic parameters correlate with the degree of placental insufficiency.